Dampak Penerapan Pertanian Organik Terhadap Kualitas Tanah dan Hasil Pertanian Tanaman Padi Sawah di Kepulauan Nias - Ida Astina Laia; Ester Agustin Kasih Damai Gulo; Lukas Lisman Gulo; Ailer Beniah Ndraha (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Organic farming is increasingly being looked at as a solution to improve soil quality and produce sustainable agriculture. This study aims to explore the impact of organic farming on soil quality and yields of wet-rice farming in Nias Islands. Based on existing research, organic farming systems are proven to provide great benefits to soil fertility, including by increasing organic matter content, boosting soil microbial activity, and improving soil structure. The use of techniques such as crop rotation, organic fertilizers and mulching have been shown to improve soil quality, increase its ability to store water and reduce erosion. In addition, more diverse and active soil microbes also contribute to more efficient nutrient cycling, reducing dependence on synthetic fertilizers and helping to control pests naturally. While the initial adoption of organic farming may result in lower yields, research shows that in the long run, yields increase as soil quality improves. Organic farming also offers better resilience to climate change, especially in terms of the soil's ability to retain water and reduce the impact of drought. Thus, organic farming in Nias Islands can not only increase agricultural productivity, but also support environmental sustainability. Therefore, the application of organic farming is the right choice to improve food security and preserve nature in Nias Islands